Shaking Things Up: On the Stability of Risk and Time Preferences - Michel Beine; Gary Charness; Arnaud Dupuy; Majlinda Joxhe (Center for Economic Studies and ifo Institute (CESifo), 2020)
We conduct a survey and incentivized lab-in-the-field experimental tasks in Tirana, Albania. While the original purpose of our study was to examine whether and how deep parameters such as time and risk preferences affect the intention to migrate, our study was transformed into a natural experiment owing to two large earthquakes that shook the Tirana area during our data-collection period. These events provide us with a rare opportunity to gather evidence (including a pre-earthquake control) on the effect of natural disasters on time and risk preferences. We find unambiguous effects towards more risk aversion and impatience for affected individuals. Moreover, as it turns out, the second earthquake amplified the effect of the first one, suggesting that experiences cumulate in their influence on these preferences.
Keywords: B49; C90; D91; F22; 330; time preferences; risk preferences; natural disaster; Albania; migration